ANALYSIS OF CONSUMER PERCEPTION AND BRAND IMAGE TO CONSUMER LOYALTY BY ONLINE-BASED TRAVEL APP - Astuti, Enny Diah; Hastuti, Sri (International Journal of Multidisciplinary Research and Literature, 2022)
This research aims to find out and analyze consumer perception and brand image towards consumer loyalty simultaneously in online travel application customers. The type of research used is a quantitative approach. The study results show that consumer perception partially affects consumer loyalty in online-based travel applications. Brand image partially affects consumer loyalty in online-based travel applications. Consumer perception and brand image simultaneously affect consumer loyalty in online-based travel applications. The ability of price variables and brand image can explain the variation of consumer loyalty by 64.2%. Other variables explain the remaining 35.8% outside of research that other researchers can develop later.